Docosahexaenoic acid supplementation of preterm infants and parent-reported symptoms of allergic disease at 7 years corrected age: follow-up of a randomized controlled trial. Issue 6 (9th May 2019) - Gunaratne, Anoja W; Makrides, Maria; Collins, Carmel T; Gibson, Robert A; McPhee, Andrew J; Sullivan, Thomas R; Gould, Jacqueline F; Green, Tim J; Doyle, Lex W; Davis, Peter G; French, Noel P; Colditz, Paul B; et al.
ABSTRACT: Background: Docosahexaenoic acid (DHA, 22:6n–3) supplementation in the prenatal period is associated with a reduction in the incidence of some symptoms of allergic disease. Infants born preterm are at increased risk of allergic disease, but it is unknown if DHA supplementation reduces the risk of childhood allergies. Objectives: The aim of this study was to determine if supplementation of infants born at <33 wk gestation with high-DHA compared with standard-DHA enteral feeds decreases the incidence and severity of parent-reported allergic disease symptoms at a corrected age (CA) of 7 y. Methods: This study was a follow-up of an Australian multicenter randomized controlled trial. Infants were given high-DHA (∼1% total fatty acids) or standard-DHA (∼0.3% total fatty acids) enteral feeds from 2–4 d of postnatal age until 40 wk postmenstrual age. Parent-reported incidence of respiratory allergic disease symptoms including wheeze and rhinitis at 7 y CA were the main outcomes. Other outcomes included the incidence of eczema symptoms; severity of any symptoms; and the incidence of wheeze, rhinitis, rhinoconjunctivitis, and eczema from birth to 7 y CA. Results: Data were available for 569 of 657 (87%) children originally randomized. Symptoms of wheeze or rhinitis at 7 y CA did not differ between high- and standard-DHA groups [wheeze: RR: 1.10; 95% CI: 0.73, 1.65; P = 0.66; rhinitis: RR: 1.09; 95% CI: 0.81, 1.46; P = 0.59]. There was no difference in other allergic disease symptoms at 7 y CA or in the severity of symptoms. Parent-reported symptoms of wheeze, rhinitis, rhinoconjunctivitis, or eczema from birth to 7 y CA did not differ between the groups. Conclusions: High-dose DHA supplementation of infants born at <33 wk gestation did not alter allergic disease symptoms or severity at 7 y CA, or from birth to 7 y CA compared with standard-dose DHA. This trial was registered with the Australian New Zealand Clinical Trials Registry as ANZCTR 12606000327583 (http://www.anzctr.org.au ).